Prevalence of Serum Celiac Antibodies in a Multiracial Asian Population-A First Study in the Young Asian Adult Population of Malaysia - Yap, T.W.C.; Chan, W.K.; Leow, A.H.R.; Azmi, A.N.; Loke, M.F.; Vadivelu, J.; Goh, K.L. (Public Library of Science, 2015)
Background: Celiac disease (CD) is an immune-mediated disorder induced by the ingestion of gluten in genetically susceptible persons. The prevalence of CD in Malaysia is unknown. We aim to determine the seroprevalence of CD antibodies and also investigate the correlation between H. pylori infection and CD in the young and healthy multiracial Malaysian population. Methods: Healthy young adult volunteers between the ages of 18-30 years were consecutively recruited from June 2012 to May 2014 at the University of Malaya Medical Centre (UMMC), Kuala Lumpur. Serum samples from all the participants were tested for anti-gliadin antibody immunoglobulin A/immunoglobulin G (IgA/IgG) and anti-tissue transglutaminase antibody (tTG) IgA/IgG. Samples positive for both anti-gliadin and anti-tTG were further validated for anti-human endomysial IgA antibodies (EmA). Serological diagnosis of CD was made when anti-gliadin, anti-tTG and anti-EmA were positive. Results: 562 qualified participants with mean age 24 ± 2.4 years old were recruited into our study. CD was found in 7 participants where most of them were asymptomatic and unaware of their CD status. The median of anti-gliadin and anti-tTG IgA/IgG value was 38.2 U/ml (interquartile range, 28.3-60.4 U/ml) and 49.2 U/ml (interquartile range, 41.1-65.9 U/ml), respectively. Seroprevalence of CD antibodies was 1.9% (6 out of 324) in female while only 0.4% (1 out of 238) in male. Seroprevalence among Malay was 0.8% (2 of 236), Chinese was 1.7% (3 of 177) and Indian was 1.3% (2 of 149). Overall, seroprevalence of CD antibodies in healthy asymptomatic adults in the Malaysian population was 1.25% (95% CI, 0.78%-1.72%). No significant relationship was discovered between CD and H. pylori infection. Conclusions: The seroprevalence of CD antibodies in healthy young adults in the Malaysian population was 1.25% (1 in 100). CD is underdiagnosed and it could be a much greater problem in Malaysia than previously thought.